DETERMINAN KINERJA KEUANGAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Elrachma, Zafirah Firdausi; Ekowati, Wiwik Hidajah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to obtain empirical evidence of the effect of financial ratio factors including Non-Performing Loans (NPL), Loan Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), and size of the bank on financial performance. The study population involves conventional general banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2021, from which the samples of 40 companies are selected through purposive sampling method and consist of 186 data analyzed by multiple regression utilizing SPSS 26 software. The results exhibited that the Non-Performing Loan (NPL) had a negative correlation effect on financial performance; the size of the bank had a positive correlation effect on financial performance. However, the Loan Deposit Ratio (LDR) and Capital Adequacy Ratio (CAR) proved to have no effect on financial performance.